The atmospheric conditions of hot and mild deserts to be geoengineered - Sevilmis, Ugur (My University, 2020)
Excess evaporation due to hot, dry and sunny atmosphere with low precipitation and low water holding capacity in ground results with hot hyper arid zones in the world. Sahara, Australia and Arabian deserts are top three covering 9 billion, 2.7 billion and 2.3 billion ha respectively. This paper describes the current knowledge on general atmospheric circulations as a base to a theory to geoengineer the atmosphere to send the climate of Sahara back to 6.000 years ago where tropical grasslands were dominating.
Supplemental Materials: https://osf.io/u4b8r/
Keywords: African Humid Period; Desert; geoengineering; humidity; temperature